Influence of age on patellar tendon reflex response - Chandrasekhar, A.; Abu Osman, Noor Azuan; Tham, L.K.; Lim, K.S.; Wan Abas, Wan Abu Bakar (Public Library of Science, 2013)
BACKGROUND: A clinical parameter commonly used to assess the neurological status of an individual is the tendon reflex response. However, the clinical method of evaluation often leads to subjective conclusions that may differ between examiners. Moreover, attempts to quantify the reflex response, especially in older age groups, have produced inconsistent results. This study aims to examine the influence of age on the magnitude of the patellar tendon reflex response. METHODOLOGY/PRINCIPAL FINDINGS: This study was conducted using the motion analysis technique with the reflex responses measured in terms of knee angles. Forty healthy subjects were selected and categorized into three different age groups. Patellar reflexes were elicited from both the left and right patellar tendons of each subject at three different tapping angles and using the Jendrassik maneuver. The findings suggested that age has a significant effect on the magnitude of the reflex response. An angle of 45° may be the ideal tapping angle at which the reflex can be elicited to detect age-related differences in reflex response. The reflex responses were also not influenced by gender and were observed to be fairly symmetrical.